Advancing Community-Based Education: Strategies, Challenges, and Future Directions for Scaling Impact in Higher Education - Sudipta Chowdhury; Ammar Alzarrad (Trends in Higher Education)
Community-Based Education (CBE) is a transformative approach that integrates academic learning with practical problem-solving by engaging students in real-world community challenges. This study, grounded in a comprehensive literature review, first examines the distinctive characteristics of CBE relative to traditional pedagogical frameworks, exploring its application across varied educational contexts and the implementation challenges it faces. In particular, the research investigates the complexities of aligning community projects with established technical standards and overcoming institutional resistance while also assessing the effectiveness of CBE in cultivating socially responsible, career-ready graduates. To ensure that these findings are both relevant and practical, the study then incorporates validation from an expert review panel consisting of educators and administrators. These experts provided firsthand insights into the challenges they have encountered and shared potential strategies for addressing them, which in turn informed the development of a robust set of guidelines and recommendations. The recommendations underscore the importance of forging strong community partnerships, offering targeted faculty development opportunities, and maintaining curricular flexibility to effectively integrate real-world learning experiences. Ultimately, the study reinforces the pivotal role of CBE in preparing future leaders capable of making a positive impact at both local and global levels.